Effect of Temperature on Triplet Exciton Migration in Langmuir–Blodgett Films - Ibraev, N. Kh. (Nauka/Interperiodica, 2002)
The effect of temperature on delayed annihilation fluorescence of aromatic molecules in Langmuir–Blodgett films has been studied. It is shown that because of the inhomogeneous broadening of energy levels caused by local nonuniformities in the film structure, the migration efficiency of triplet excitons is temperature dependent. Experimental data were used to calculate the scatter in the triplet level energies of the anthracene, 1,2-benzanthracene, and fluoranthene molecules. © 2002 MAIK “Nauka/Interperiodica”.